IMPLEMENTATION OF SERVANT LEADERSHIP AT GMIM SYALOM LELEMA: THE EFFECT OF LEADERS' ATTITUDES OF SERVICE ON CONGREGATION ATTENDANCE AT WORSHIP SERVICES - Eunike Karunia Natasya Sumual (Philosophy Global: International Journal of Christian and Catholic Philosophy, 2025)
This study examines the implementation of Servant Leadership within GMIM Syalom Lelema and its influence on congregational attendance in worship fellowship. Rooted in the theological model of leadership exemplified by Jesus Christ, Servant Leadership emphasizes humility, empathy, presence, and service as core leadership values. Using a qualitative case-study approach, data were collected through observations, interviews, and documentation to understand the relational dynamics between church leaders and congregational participation. The findings reveal that the congregation highly values leaders—pastors, elders, and deacons—who demonstrate genuine care, pastoral presence, and willingness to serve. Acts of pastoral visitation, listening to members’ struggles, and showing humility significantly strengthen emotional and spiritual bonds within the community, resulting in higher attendance and engagement in various worship activities. Conversely, leaders who lack servant-like attitudes tend to receive weaker responses from the congregation, which negatively impacts their participation in worship. The study concludes that Servant Leadership is not merely a theological ideal but a practical necessity within the communal culture of GMIM Syalom Lelema. The model effectively fosters stronger relationships, increases congregational commitment, and enhances the vitality of church fellowship. Keywords: Servant Leadership, Pastoral Ministry, Worship Attendance, Ecclesial Leadership, GMIM Syalom Lelema.